Slope of a del Pezzo surface with du Val singularities. (7th December 2012) - Won, Joonyeong
Abstract : We classify all slope stabilities on a del Pezzo surface ( S, − K S ) with du Val singularities. As an application, we have new kinds of non‐Kähler–Einstein surfaces.